2x+3=-6(-7x+7)-242

Simple and best practice solution for 2x+3=-6(-7x+7)-242 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+3=-6(-7x+7)-242 equation:



2x+3=-6(-7x+7)-242
We move all terms to the left:
2x+3-(-6(-7x+7)-242)=0
We calculate terms in parentheses: -(-6(-7x+7)-242), so:
-6(-7x+7)-242
We multiply parentheses
42x-42-242
We add all the numbers together, and all the variables
42x-284
Back to the equation:
-(42x-284)
We get rid of parentheses
2x-42x+284+3=0
We add all the numbers together, and all the variables
-40x+287=0
We move all terms containing x to the left, all other terms to the right
-40x=-287
x=-287/-40
x=7+7/40

See similar equations:

| 3/15=1/x=x/10 | | 2t2+13t+11=0 | | 4x+5-2x+2=13 | | 3x+x-2x+7=x=15 | | x÷3+6.4=10.2 | | 3(4-4v)=48 | | 15=2x9+4+3 | | y/2+y/4=8/9 | | -3y-7=5 | | 3x+3=5x-10+1 | | -3p+15-3p=-37 | | 1/3.x+1/3=1-1/3.x | | -7(w+1)-(4+6w)=-14w | | -8x+4-5x=-35 | | 9x+19+3x+3+x-11=180 | | 5x-2=-9+x | | (-x2-1)-2x=-4 | | 1/3y-11=1/9y | | 42=3x+3(4-4x) | | 5x+7=-2x-49 | | 6x²-6x-12=0 | | 2x2-6x+3=0 | | 2x+6(4x-10)=70 | | r/3.2=2.7/2.4 | | c−5=- | | x*8=54 | | 2k+4(4k+2)=62 | | 10-d=16 | | 5x+5(2x-11)=35 | | 8(x-4)+8=8x+6 | | 7x+5(5x-9)=243 | | .3*9=6*x |

Equations solver categories